Injecting-related health harms and overuse of acidifiers among people who inject heroin and crack cocaine in London: a mixed-methods study - Magdalena Harris; Jenny Scott; Talen Wright; Rachel Brathwaite; Daniel Ciccarone; Vivian Hope (BMC, 2019)
Abstract Background Venous access is a priority for people who inject drugs (PWID). Damage and scarring of peripheral veins can exacerbate health harms, such as skin and soft tissue infections (SSTI), and promote transitions to femoral and subcutaneous injecting. Brown heroin available in Europe requires acidification for injection preparation. In this paper, we present mixed-methods data to explore our hypothesis of a link between overly acidic injection solutions, venous damage and SSTI risk. Methods We present a structured survey (n = 455) and in-depth qualitative interview (n = 31) data generated with PWID in London for the Care & Prevent study. Participants provided life history data and detail on injecting environments and drug preparation practices, including the use of acidifiers. Bivariate and multivariate analyses were conducted using a logistic regression for binary outcomes to explore associations between outcomes and excessive acidifier use. Grounded theory principles informed inductive qualitative analysis. Mixed-methods triangulation was iterative with results comparison informing the direction and questions asked of further analyses. Results Of the 455 participants, most (92%) injected heroin and/or crack cocaine, with 84% using citric as their primary acid for drug preparation. Overuse of acidifier was common: of the 418 who provided an estimate, 36% (n = 150) used more than ½ a sachet, with 30% (n = 127) using a whole sachet or more. We found associations between acidifier overuse, femoral injecting and DVT, but not SSTI. Qualitative accounts highlight the role of poor heroin quality, crack cocaine use, information and manufacturing constraints in acidifier overuse. Painful injections and damage to peripheral veins were common and often attributed to the use of citric acid. Conclusions To reduce injecting-related injury and associated consequences, it is crucial to understand the interplay of environmental and practice-based risks underpinning venous damage among PWID. Overuse of acidifier is a modifiable risk factor. In the absence of structural supports such as safe injecting facilities or the prescribing of pharmaceutical diamorphine, there is an urgent need to revisit injecting paraphernalia design and distribution in order to alleviate health harms and distress among the most marginalised.